2017
DOI: 10.1016/j.actbio.2017.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory polyurethanes with oxidation-induced degradation: In vivo and in vitro correlations for endovascular material applications

Abstract: The synthesis of thermoset shape memory polymer (SMP) polyurethanes from symmetric, aliphatic alcohols and diisocyanates has previously demonstrated excellent biocompatibility in short term in vitro and in vivo studies, although long term stability has not been investigated. Here we demonstrate that while rapid oxidation occurs in these thermoset SMPs, facilitated by the incorporation of multi-functional, branching amino groups, byproduct analysis does not indicate toxicological concern for these materials. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
194
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(215 citation statements)
references
References 47 publications
(89 reference statements)
18
194
1
Order By: Relevance
“…It is noteworthy that G25 had the slowest degradation rate, which is due to the oxidatively stable structure of Gly. Previous research has demonstrated that in oxidative conditions, the tertiary amines in TEA and HPED are oxidized to amine oxide to form primary amines, carboxylic acids, and aldehydes (Weems, Wacker, Carrow, Boyle, & Maitland, ). This research explains why the control TEA‐based foams (T30, T40, and T60), which contain higher percentage of tertiary amines, are more susceptible to oxidation than the Gly‐based foam (G25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that G25 had the slowest degradation rate, which is due to the oxidatively stable structure of Gly. Previous research has demonstrated that in oxidative conditions, the tertiary amines in TEA and HPED are oxidized to amine oxide to form primary amines, carboxylic acids, and aldehydes (Weems, Wacker, Carrow, Boyle, & Maitland, ). This research explains why the control TEA‐based foams (T30, T40, and T60), which contain higher percentage of tertiary amines, are more susceptible to oxidation than the Gly‐based foam (G25).…”
Section: Resultsmentioning
confidence: 99%
“…More significant differences were observed between the ester‐containing foams and their controls over time in oxidative degradation conditions. Previously, our group analyzed degraded SMP foams and their degradation products and proposed an oxidative degradation mechanism for HPED and TEA; the tertiary amine oxidizes into amine‐oxide, which further undergoes C–N fragmentation leading to the formation of carboxylic acids and aldehydes (Weems et al, ). All TEA‐based foams showed carbonyl peak shifts from 1,689 cm −1 to 1,696 cm −1 (Figure b) which are attributed to the fragmentation of C‐N bond from the tertiary amine of TEA or HPED to form carboxylic acid or aldehyde conjugates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional benefit to phenolic acids is their antioxidant properties; phenolic acids contain hydrogen donating groups that scavenge free radicals and reduce oxidation . Recently, we found that SMP foams are susceptible to oxidative degradation . Thus, in future work, we will obtain oxidative degradation profiles of phenolic acid‐containing SMP foams in addition to expanding the library of phenolic acids utilized in SMP foaming to further characterize their tunability.…”
Section: Discussionmentioning
confidence: 99%
“…They can present different behaviors depending on their synthetic conditions and have considerable permeability, mainly since it can be controlled according to the ratio of their hydrophobic and hydrophilic chain moieties . Some of these PUs are highly researched because of their ability to biodegrade …”
Section: Introductionmentioning
confidence: 99%